Study of Agricultural Development in a Dry Region: A Regional Analysis of Jhunjhunu District (Rajasthan): अर्ध-शुष्क क्षेत्र में कृषि विकास का अध्ययन: झुंझुनू जिला (राजस्थान) का एक क्षेत्रीय विश्लेषण - Kumar, Rajesh; Janu, Dharmveer (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
In the present research paper, a regional and analytical study of agricultural development in Jhunjhunu district, located in the semi-arid region of Rajasthan, has been conducted. In this semi-arid climatic region, natural conditions such as limited and irregular rainfall, high temperature, and high rate of evaporation directly affect the direction and stability of agricultural production. Due to the absence of canal irrigation and uncertainty of rainfall in the district, agriculture mainly depends on groundwater-based irrigation, which leads to fluctuations in production and regional imbalance. The study reveals that there is a significant difference in cropping pattern and agricultural productivity between irrigated and non-irrigated areas. In areas where irrigation facilities are available through tube wells and wells, the production of rabi crops—such as wheat, gram, and mustard—is found to be higher and more stable, whereas in rain-dependent areas, kharif crops—such as bajra, moong, moth, and guar—remain dominant. The continuous decline in groundwater level has emerged as a serious challenge for agriculture in the district, which is the result of excessive exploitation, limited recharge capacity, and lack of water conservation measures. In addition, soil erosion and decline in land fertility due to strong winds, low vegetation cover, and improper agricultural practices also affect agricultural productivity. Lack of technical awareness, predominance of small and marginal farmers, and limited capacity for agricultural investment are also major socio-economic factors slowing down the pace of agricultural development. Abstract in Hindi Language: प्रस्तुत शोध-पत्र में राजस्थान के अर्ध-शुष्क क्षेत्र में स्थित झुंझुनू जिले के कृषि विकास का क्षेत्रीय एवं विश्लेषणात्मक अध्ययन किया गया है। अर्ध-शुष्क जलवायु वाले इस क्षेत्र में सीमित एवं अनियमित वर्षा, उच्च तापमान तथा अधिक वाष्पीकरण दर जैसी प्राकृतिक परिस्थितियाँ कृषि उत्पादन की दिशा और स्थिरता को प्रत्यक्ष रूप से प्रभावित करती हैं। जिले में नहर सिंचाई के अभाव तथा वर्षा की अनिश्चितता के कारण कृषि मुख्यतः भूजल आधारित सिंचाई पर निर्भर रहती है, जिससे उत्पादन में उतार-चढ़ाव तथा क्षेत्रीय असंतुलन की स्थिति उत्पन्न होती है। अध्ययन से यह स्पष्ट हुआ कि सिंचित एवं असिंचित क्षेत्रों में फसल प्रतिरूप तथा कृषि उत्पादकता के स्तर में उल्लेखनीय अंतर पाया जाता है। जिन क्षेत्रों में ट्यूबवेल एवं कुओं के माध्यम से सिंचाई सुविधाएँ उपलब्ध हैं, वहाँ रबी फसलों—जैसे गेहूँ, चना और सरसों—का उत्पादन अधिक एवं स्थिर पाया गया, जबकि वर्षा पर निर्भर क्षेत्रों में खरीफ फसलों—जैसे बाजरा, मूंग, मोठ और ग्वार—की प्रधानता बनी रहती है। भूजल स्तर में निरंतर गिरावट जिले की कृषि के लिए एक गंभीर चुनौती के रूप में सामने आई है, जो अत्यधिक दोहन, सीमित पुनर्भरण क्षमता तथा जल संरक्षण उपायों की कमी का परिणाम है। इसके अतिरिक्त तेज हवाओं, कम वनस्पति आवरण तथा अनुचित कृषि पद्धतियों के कारण मृदा अपरदन और भूमि की उर्वरता में गिरावट भी कृषि उत्पादकता को प्रभावित करती है। तकनीकी जागरूकता की कमी, छोटे एवं सीमांत किसानों की अधिकता तथा कृषि निवेश की सीमित क्षमता भी कृषि विकास की गति को धीमा करने वाले प्रमुख सामाजिक-आर्थिक कारक हैं। Keywords: कृषि परिदृश्य, कृषि विकास, कृषि उन्नति, झुंझुनू जिला, भूमि उपयोग परिवर्तन, सिंचित एवं असिंचित कृषि, फसल प्रतिरूप, जल संसाधन एवं भूजल स्तर।